The House of Habsburg - Wandruszka, Adam. (New York Doubleday and Company, Inc., 1964)
It is special achievement of this book to present that history in succinct but colorful form from Rudolph I, who established the familys position on the upper Rhine; through Charles V, who ruled an empire on which the sun truly never set to Francis Joseph, "the last monarch of the old school".
Keywords: Politics